2018
DOI: 10.1186/s12955-018-0878-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Audit of Diabetes-Dependent Quality of Life (ADDQoL) in a population-based sample of Polish adults with type 1 and 2 diabetes

Abstract: BackgroundThe aim of the present paper was the assessment of the psychometric properties of the Polish language version of the Audit of Diabetes-Dependent Quality of Life (ADDQoL) questionnaire applied in Poland among patients with type 1 (T1DM) or type 2 diabetes (T2DM).MethodsThe studies were carried out among 330 patients with diabetes including 115 with T1DM and 215 with T2DM. In all the patients the level of the quality of life was investigated using the Polish language version of the ADDQoL and the psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…Our study provides information on diabetes-related QoL and its evaluation by patients with T2DM in Poland, Slovakia, and the Czech Republic, based on a study using the ADDQoL, a broadly used, DM-specific scale. [9][10][11][12][13]19,23 In the literature, one can find papers on patients from specific countries, but comparative analyses are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study provides information on diabetes-related QoL and its evaluation by patients with T2DM in Poland, Slovakia, and the Czech Republic, based on a study using the ADDQoL, a broadly used, DM-specific scale. [9][10][11][12][13]19,23 In the literature, one can find papers on patients from specific countries, but comparative analyses are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The study in Poland relied on the Polish language version of the ADDQoL, as its psychometric properties, determined earlier, indicate that it is a reliable tool for the assessment of QoL in adult Polish patients with T1DM or T2DM. 19 The other parts of the study relied on the Czech and Slovak versions of the ADDQoL. The license number for the Czech language version was CB636, and for the Slovak version it was CB638.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The license for the Polish language version bore the number CB521). The studies applied the Polish language version of the ADDQoL, the psychometric properties of which, determined earlier, indicate that it is a reliable tool useful for the assessment of the level of QoL of adult patients in Poland with T1DM or T2DM [26].…”
Section: Methodmentioning
confidence: 99%
“…Taking into account the fact that in the individual countries the study populations of patients with diabetes differed in terms of socio-demographic, ethnicity, cultural, lifestyle and medical care, the determination of their QoL required determining the psychometric properties of the questionnaire written in the mother tongue of the assessed population. It has been shown that the results of the psychometric properties of ADDQoL have proved that this questionnaire is a reliable tool for a comprehensive evaluation of the QoL in adults with diabetes [25] -also in Polish language version [26]. In many studies considering the QoL of patients with diabetes the ADDQoL was used [22,19,25].…”
Section: Introductionmentioning
confidence: 99%